Pengaruh Upah Minimum dan Angkatan Kerja Terhadap Tingkat Pengangguran Terbuka di Indonesia 2014-2023 - Anggi Erlangga; M. Reza Falevi; Priliyanti Putri; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Improper population management will cause population problems, especially in work areas. Existing jobs have not been able to meet the employment needs resulting from the unemployment problem. The number of unemployed in Indonesia reaches 7 million people from the workforce. The aim of this research is to determine the effect of economic growth, minimum wage labor and inflation on unemployment in Indonesia. The analysis technique used is multiple linear regression, using time sequential data for 2014-2023. The test results show that with a 95 percent confidence level the model is significant, indicated by a significance value of F 0.000 < 0.02. Determination coefficient of The R Square for the model obtained a figure of 0.235 which indicates the independent variable. The model is able to explain 95 percent of the variation in endogenous variables well. Meanwhile, the remaining 5 percent is explained by other variables outside these variables model. This means that together the variables are inflation, economic growth and minimum wage workers influence the level of open unemployment. Partially, of the three variables tested by considering the P-value results, there are two Variables that influence the open unemployment rate are inflation and minimum wages worker. Meanwhile, the economic growth variable has no effect on the level of openness unemployment.